Assessment of Holothuria arguinensis feeding rate, growth and absorption efficiency under aquaculture conditions - DOMINGUEZ GODINO, JORGE ANTONIO (2020)
Holothuria arguinensis is a potential species for sea cucumber aquaculture in Europe. In a first experiment, feeding rate (FR), growth, absorption efficiency (AE) and survival of adults (135.01 +/- 10.87g eviscerated weight) were assessed under sediment tank conditions. In a second experiment, the feasibility to use sea bream (Sparus aurata) biodeposits as a food source was studied for adults (168.69 +/- 14.59g eviscerated weight). Individuals in the first experiment showed an increase of weight (specific growth rate (SGR)=0.2% d(-1)), positive FRs and mean value of AE close to 80% with a mean organic matter content of 90.07 +/- 11.5mg/g in the offered sediment. Sea cucumbers fed with fish biodeposits showed a reduction of weight (SGR<-0.14%d(-1)), low FRs and negative values of AE. The influence of low salinity and temperature during experiments should be considered to explain these results. Indeed, sea cucumbers can be affected by a decrease of these parameters during winter months resulting in a period of inactivity.